Molecular Parameters and Transmembrane Transport Mechanism of Imidazolium‐Functionalized Binols. Issue 32 (7th July 2014) - Vidal, Marc; Schmitzer, Andreea
Abstract We describe the molecular parameters governing the transmembrane activity of imidazolium‐functionalized anion transporters and present a detailed mechanistic study. These ionophores adopt a mobile‐carrier mechanism for short methyl and butyl chains, a combined mobile‐carrier/transmembrane‐pore mechanism for octyl and dodecyl chains, and form transmembrane aggregates for hexadecyl chains.